Modified high nickel ternary positive electrode material and method for producing the same, and power consumption device

The modified high nickel ternary cathode material, with a core doped with M1, M2, and W, and coated with specific compounds, addresses the structural instability of high nickel electrodes, enhancing cycle and storage performance of lithium ion batteries.

JP7617264B2Active Publication Date: 2025-01-17CONTEMPORARY AMPEREX TECHNOLOGY (HONG KONG) LIMITED
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023526409
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-09-18
Filing Date
2022-06-01
Publication Date
2025-01-17
Estimated Expiration
2042-06-01

AI Technical Summary

Technical Problem

The structural stability of high nickel ternary positive electrode materials deteriorates with increasing nickel content, adversely affecting the cycle performance and storage performance of lithium ion secondary batteries.

Method used

A modified high nickel ternary cathode material is developed, comprising an inner core doped with M1, M2, and W, and coated with a Co-containing compound, an Al-containing compound, and a B-containing compound, to enhance structural stability and reduce impurity lithium content.

Benefits of technology

The modified material improves cycle performance, thermal stability, and storage performance of lithium ion secondary batteries by reducing interfacial side reactions and maintaining high capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007617264000009
    Figure 0007617264000009
  • Figure 0007617264000010
    Figure 0007617264000010
  • Figure 0007617264000011
    Figure 0007617264000011
Patent Text Reader

Abstract

The present application provides a modified high-nickel ternary positive electrode material, which includes an inner core and two inner and outer coating layers, the inner core including a high-nickel ternary positive electrode material substrate, the substrate being doped with M1, M2 and W, wherein M1 is one of Mo, Zr, Ti, Sb, Nb and Te, and M2 is one of Mg, Al, Ca, Zn and Sr, and the chemical formula of the high-nickel ternary positive electrode material substrate doped with M1, M2 and W is Li 1+a [Ni x Co y Mn z M1 b M2 c W d ]O2, where 0.65≦x<1, 0≦y<0.3, 0≦z<0.3, 0
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application relates to the field of lithium battery technology, in particular to a modified high-nickel ternary positive electrode material and its manufacturing method, a secondary battery, a battery module, a battery pack and a power consuming device. [Background technology]

[0002] 2. Description of the Related Art With the rapid development of the new energy field, lithium ion secondary batteries, due to their advantages such as excellent electrochemical performance, no storage effect, and little environmental pollution, are widely used in various large power devices, energy storage systems, and various consumer products, especially in the new energy automobile field such as pure electric vehicles and hybrid electric vehicles.

[0003] Due to the rapid development of lithium ion secondary batteries, there are higher requirements for their energy density, cycle performance and safety performance. Meanwhile, high nickel positive electrode active materials are recognized as the optimal choice to meet the high energy density requirements. However, with the continuous increase in nickel content, the structural stability is increasingly worse, which further affects the cycle performance and storage performance of lithium ion secondary batteries.

[0004] Therefore, there is a demand for improving the capacity of lithium ion secondary batteries while ensuring the cycle performance and storage performance of the secondary batteries. Summary of the Invention [Problem to be solved by the invention]

[0005] In view of the technical problems existing in the background art, the present application aims to provide a modified high-nickel ternary positive electrode material, and a lithium-ion secondary battery manufactured using the same has high capacity and improved cycle performance and storage performance. [Means for solving the problem]

[0006] To achieve the above object, according to the first aspect of the present application, a modified high-nickel ternary cathode material is provided, which material includes an internal core and an inner and outer double coating layer. The internal core includes a high-nickel ternary cathode material substrate, and the substrate is doped with M1, M2, and W. Here, the M1 is one of Mo, Zr, Ti, Sb, Nb, and Te, and the M2 is one of Mg, Al, Ca, Zn, and Sr. The chemical formula of the high-nickel ternary cathode material substrate doped with M1, M2, and W is Li 1+a [Ni x Co y Mn z M1 b M2 c W d O 2 where 0.65 ≦ x < 1, 0 ≦ y < 0.3, 0 ≦ z < 0.3, 0 < a < 0.2, 0 < b < 0.1, 0 < c < 0.1, 0 < d < 0.1, and x + y + z + b + c + d = 1, and optionally 0.8 ≦ x < 1. The surface layer of the internal core is also doped with Co. The inner coating layer is a Co-containing compound, and the outer coating layer is an Al-containing compound and a B-containing compound.

[0007] Compared with the prior art, the present application includes at least the beneficial effects described below.

[0008] This application can more effectively enhance the structural stability of the high-nickel ternary cathode material by co-doping three types of ions (i.e., M1, M2, and W) into the high-nickel ternary cathode material substrate, thereby significantly improving the cycle performance and thermal stability of the secondary battery. This application can effectively reduce the content of expensive nickel ions on the surface layer of the high-nickel ternary cathode material by doping Co on the surface layer of the high-nickel ternary cathode material, thereby reducing the side reaction between expensive nickel ions and the electrolyte, and further improving the cycle performance and storage performance of the secondary battery. This application further uniformly coats the high-nickel ternary cathode material with an inner layer of Co-containing compound, an outer layer of Al-containing compound, and B-containing compound, thereby effectively reducing the content of impurity lithium on the surface, and further effectively suppressing the interfacial side reaction between the high-nickel ternary cathode material and the electrolyte, thereby improving the capacity and rate performance of the high-nickel ternary cathode material, and further improving the cycle, storage, and safety performance of the secondary battery.

[0009] In any embodiment, the doping amount of M1 ≥ the doping amount of M2 or W.

[0010] In any embodiment, the ratio of the doping amount of M1 to the sum of the doping amounts of M2 and W is 1:(0.1 - 2), and optionally 1:(0.5 - 1.5).

[0011] When the ratio of the doping amount of M1 to the sum of the doping amounts of M2 and W is controlled within a predetermined range, it can be ensured that the high-nickel ternary cathode material has a relatively high capacity, and the structural stability of the material can be maximally enhanced, thereby further improving the cycle performance of the secondary battery.

[0012] In any embodiment, the thickness d of the surface layer satisfies 0 < d < 3 μm, and optionally 0 < d < 2 μm. When the thickness d of the surface layer is within a predetermined range, the cycle performance of the secondary battery can be further improved.

[0013] In any embodiment, the sum of the surface doping amount of Co and the coating amount of the Co-containing compound is 100-20000 ppm, optionally 1000-13000 ppm, the coating amount of the Al-containing compound is 100-3000 ppm, optionally 500-2000 ppm, and the coating amount of the B-containing compound is 100-2000 ppm, optionally 500-1500 ppm, where both the surface doping amount and the coating amount are calculated in terms of the corresponding element in the compound for the modified high nickel ternary cathode material. When the sum of the surface doping amount of Co and the coating amount of the Co-containing compound is within a predetermined range, the cycle performance of the secondary battery can be further improved. When the coating amount of the Al-containing compound and the coating amount of the B-containing compound are within a predetermined range, the cycle performance of the secondary battery can be further improved.

[0014] In either embodiment, the total thickness of the inner and outer coating layers is 0.001-1 μm.

[0015] In any embodiment, the coating amount of the Al-containing compound and the coating amount of the B-containing compound satisfy the weight ratio of Al to B being (0.5-2:1), where each of the coating amounts is calculated as the corresponding element in the compound for the modified high nickel ternary positive electrode material. When the coating amount of the Al-containing compound and the coating amount of the B-containing compound satisfy a predetermined relationship, the capacity and cycle performance of the secondary battery can be further improved.

[0016] In any embodiment, the doping amount of W is 100-2000 ppm, optionally 100-1500 ppm, the doping amount of M1 is 2000-4000 ppm, and the doping amount of M2 is 500-2000 ppm, where each of the doping amounts is calculated as a corresponding element for the modified high nickel ternary positive electrode material. When the doping amounts of M1, M2 and W are within the predetermined ranges, the structural stability of the high nickel ternary positive electrode material can be further improved, and thus the cycle performance and storage performance of the secondary battery can be further improved.

[0017] In any embodiment, the sum of the surface doping amount of Co and the coating amount of the Co-containing compound, the Al-containing compound and the B-containing compound is 1000-22000 ppm, optionally 1000-15000 ppm, wherein the surface doping amount and the coating amount are calculated in terms of the corresponding element in the compound for the modified high nickel ternary cathode material.

[0018] In any embodiment, the volumetric particle size distribution diameter distance of the modified high nickel ternary cathode material is (Dv 90 -Dv 10 ) / Dv 50 ≧1.1, selectively (Dv 90 -Dv 10 ) / Dv 50 ≧ 1.2.

[0019] In either embodiment, the modified high nickel ternary cathode material has a powder compaction density at 5 tons of pressure of ≧3.4 g / cc, optionally ≧3.5 g / cc.

[0020] The inventors have found through testing that when the modified high-nickel ternary positive electrode material has a wide volumetric particle size distribution diameter distance and a relatively high powder compaction density, the volumetric energy density of the high-nickel ternary positive electrode material can be obviously increased.

[0021] According to a second aspect of the present application, there is further provided a method of producing a modified high nickel ternary cathode material, the method comprising: Mixing and sintering a lithium salt, a W-doped high-nickel ternary precursor, a compound containing M1, and a compound containing M2 to obtain a high-nickel ternary positive electrode material substrate doped with M1, M2, and W, wherein the chemical formula of the W-doped high-nickel ternary precursor is (Ni X Co Y Mn Z W D )(OH) 2where 0.65 ≤ X < 1, 0 ≤ Y < 0.3, 0 ≤ Z < 0.3, 0 < D < 0.1, M1 is one of Mo, Zr, Ti, Sb, Nb, Te, M2 is one of Mg, Al, Ca, Zn, Sr, and the chemical formula of the high-nickel ternary cathode material substrate doped with M1, M2, and W is Li 1+a [Ni x Co y Mn z M1 b M2 c W d O 2 where 0.65 ≤ x < 1, 0 ≤ y < 0.3, 0 ≤ z < 0.3, 0 < a < 0.2, 0 < b < 0.1, 0 < c < 0.1, 0 < d < 0.1, and x + y + z + b + c + d = 1, and optionally 0.8 ≤ x < 1, step S1, and mixing and sintering the high-nickel ternary cathode material substrate doped with M1, M2, and W with a Co-containing compound to obtain a high-nickel ternary cathode material in which Co is doped on the surface layer and the surface is coated with a Co-containing compound, step S2, and mixing and sintering the high-nickel ternary cathode material in which Co is doped on the surface layer and the surface is coated with a Co-containing compound with an Al-containing compound and a B-containing compound to obtain a modified high-nickel ternary cathode material, step S3.

[0022] In any embodiment, in step S1, the sintering temperature is 700 - 950 °C, the sintering time is 10 - 20 h, and the sintering atmosphere is air or O 2 . When the sintering temperature in step S1 is within an appropriate temperature range, the capacity, cycle performance, and storage performance of the secondary battery can be further improved.

[0023] In any embodiment, the particle size of the Co-containing compound is 0.001 - 10 μm, and optionally 0.001 - 1 μm. When the particle size of the Co-containing compound is within a predetermined range, it can be uniformly coated on the surface of the high-nickel ternary cathode material, thereby further improving the cycle performance of the secondary battery.

[0024] In any of the embodiments, in step S2, the sintering temperature is 500-800° C., optionally 550-750° C., the sintering time is 5-15 h, optionally 5-10 h, and the sintering atmosphere is air or O. 2 When the sintering temperature in step S2 is within a certain range, the Co-containing compound can react with the lithium impurities on the surface of the ternary positive electrode material, and the Co-containing compound can be tightly coated on the surface of the ternary positive electrode material, thereby reducing the lithium impurities on the surface, improving the interface side reaction, and further improving the cycle performance of the secondary battery.

[0025] In any embodiment, in step S3, the sintering temperature is 200-500° C., optionally 200-400° C., the sintering time is 5-15 h, optionally 5-10 h, and the sintering atmosphere is air or O. 2 When the sintering temperature in step S3 is within a certain range, the Al-containing compound and the B-containing compound can be firmly coated on the surface of the ternary positive electrode material, thereby improving the interface reaction of the ternary positive electrode material and further improving the cycle performance of the secondary battery.

[0026] According to a third aspect of the present application, there is provided a secondary battery comprising the modified high-nickel ternary positive electrode material of the first aspect of the present application or the modified high-nickel ternary positive electrode material produced by the method of the second aspect of the present application.

[0027] According to a fourth aspect of the present application, there is provided a battery module, the battery module including the secondary battery of the third aspect of the present application.

[0028] According to a fifth aspect of the present application, there is provided a battery pack, the battery pack including the battery module of the fourth aspect of the present application.

[0029] According to a sixth aspect of the present application, there is provided a power consumption device, the power consumption device including at least one selected from the secondary battery of the third aspect of the present application, the battery module of the fourth aspect of the present application, or the battery pack of the fifth aspect of the present application.

[0030] The battery module, battery pack and power consuming device of the present application include the secondary battery of the present application, and therefore have at least the same advantages as said secondary battery. [Brief description of the drawings]

[0031] [Figure 1] FIG. 2 is a SEM image of the modified high-nickel ternary positive electrode material obtained as prepared in Example 1-1 of the present application. [Diagram 2] 2 is the initial charge-discharge curve of the button battery made of the modified high-nickel ternary positive electrode material obtained in Example 1-1 of the present application; [Diagram 3] 2 is a comparative 25° C. cycle curve of the full battery made of the modified high-nickel ternary positive electrode material obtained by preparing Comparative Example 5-1 and Example 1-1 of the present application; [Figure 4] 4 is a comparative gas expansion curve of a full battery made of the modified high-nickel ternary positive electrode material prepared in Comparative Example 5-1 and Example 1-1 of the present invention at 70° C. during storage; [Diagram 5] 1 is a schematic diagram of a secondary battery according to an embodiment of the present application; [Figure 6] FIG. 6 is an exploded view of the secondary battery according to the embodiment of the present application shown in FIG. 5. [Figure 7] 1 is a schematic diagram of a battery module according to an embodiment of the present application; [Figure 8] 1 is a schematic diagram of a battery pack according to an embodiment of the present application; [Figure 9] FIG. 9 is an exploded view of the battery pack according to the embodiment of the present application shown in FIG. 8. [Figure 10] 1 is a schematic diagram of a power consuming device in which a secondary battery according to an embodiment of the present application is used as a power source; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0032] Hereinafter, the modified high nickel ternary positive electrode material and its manufacturing method, secondary battery, battery module, battery pack and power consumption device of the present application will be described in detail with appropriate reference to the drawings. However, unnecessary detailed description may be omitted. For example, detailed description of well-known matters and repeated description of structures that are actually the same may be omitted. This is to avoid the following description from becoming unnecessarily redundant and to allow those skilled in the art to easily understand. Note that the drawings and the following description are provided to allow those skilled in the art to fully understand the present application, and are not intended to limit the subject matter described in the claims.

[0033] The "ranges" disclosed in this application are defined in the form of lower and upper limits, and a given range is defined by selecting one lower limit and one upper limit, and the selected lower and upper limits define the boundaries of the particular range. Such defined ranges may be inclusive or exclusive of the extreme values, and may be arbitrarily combined, i.e., any lower limit may be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a particular parameter, it is understood that ranges of 60-110 and 80-120 are also envisaged. However, if 1 and 2 are listed as minimum range values, and 3, 4, and 5 are listed as maximum range values, the ranges 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5 are all envisaged. In this application, unless otherwise specified, the numerical range "ab" represents a shorthand representation of any combination of real numbers from a to b, where a and b are both real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have already been listed in this specification, and "0-5" is merely a shorthand for combinations of these numbers. Also, expressing a parameter as an integer ≧2 is equivalent to disclosing that the parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0034] Unless otherwise stated, all the embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0035] Unless otherwise stated, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0036] Unless otherwise stated, all steps in this application may be performed in sequence or randomly, preferably in sequence. For example, the method includes steps (a) and (b) means that the method may include steps (a) and (b) performed in sequence, or steps (b) and (a) performed in sequence. For example, the method mentioned may further include step (c), and step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), may include steps (a), (c) and (b), may include steps (c), (a) and (b), etc.

[0037] Unless otherwise specified, the terms "comprise" and "comprises" referred to in this application may be open ended or closed ended. For example, the terms "comprise" and "comprises" may further include or include other ingredients not listed, or may include or include only the ingredients listed.

[0038] Unless otherwise stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, "A or B" is satisfied in the following cases: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) but B is true (or exists); and A and B are both true (or exist).

[0039] [Modified high-nickel ternary cathode materials] This application provides a modified high-nickel ternary cathode material, which includes an internal core and inner and outer coating layers. The internal core includes a high-nickel ternary cathode material substrate, and M1, M2, and W are doped into the substrate. Here, M1 is one of Mo, Zr, Ti, Sb, Nb, and Te, and M2 is one of Mg, Al, Ca, Zn, and Sr. The chemical formula of the high-nickel ternary cathode material substrate doped with M1, M2, and W is Li 1+a [Ni x Co y Mn z M1 b M2 c W d O 2 , where 0.65 ≤ x < 1, 0 ≤ y < 0.3, 0 ≤ z < 0.3, 0 < a < 0.2, 0 < b < 0.1, 0 < c < 0.1, 0 < d < 0.1, and x + y + z + b + c + d = 1, and optionally 0.8 ≤ x < 1. Co is also doped on the surface layer of the internal core. The inner coating layer is a Co-containing compound, and the outer coating layer is an Al-containing compound and a B-containing compound.

[0040] By doping and coating the high-nickel ternary cathode material, this application can improve the cycle performance and safety performance of the lithium-ion secondary battery on the premise of ensuring the high capacity of the lithium-ion secondary battery.

[0041] Without wishing to be limited by any theory, firstly, the present application claims that by co-doping the high nickel ternary positive electrode material with three kinds of ions (i.e. M1, M2 and W), the structural stability of the high nickel ternary positive electrode material can be more effectively improved than that of single ion doping, thereby obviously improving the cycle performance and thermal stability of the secondary battery; secondly, the present application claims that by also doping Co into the surface layer of the high nickel ternary positive electrode material, the content of high-value nickel ions in the surface layer of the high nickel ternary positive electrode material can be effectively reduced, thereby reducing the side reaction between the high-value nickel ions and the electrolyte, and further improving the cycle performance and storage performance of the secondary battery; finally, the present application claims that by uniformly coating the high nickel ternary positive electrode material with an inner layer of a Co-containing compound and an outer layer of an Al-containing compound and a B-containing compound, the content of impurity lithium on the surface can be effectively reduced, and the impurity lithium and the Co-containing compound can be effectively doped with Li. 2 Chief of Staff 3 and LiBO 2 , LiB 3 O 5 , Li 2 B 4 O 7 or a mixture thereof can be produced to convert the impurity lithium into active lithium, thereby improving the capacity and rate performance of the high-nickel ternary positive electrode material; and through the synergistic effect of the inner layer of the Co-containing compound with the outer layer of the B-containing compound and the Al-containing compound, the interfacial side reaction between the high-nickel ternary positive electrode material and the electrolyte can be more effectively inhibited, thereby further effectively improving the cycle, storage and safety performance of the secondary battery.

[0042] As a result of intensive research, the present inventors have found that, in addition to satisfying the above design conditions, when the modified high-nickel ternary positive electrode material of the present application further selectively satisfies one or several of the following conditions, the performance of the high-nickel ternary positive electrode material can be further improved.

[0043] In some embodiments, the doping amount of M1 is greater than or equal to the doping amount of M2 or W.

[0044] In some embodiments, the ratio of the doping amount of M1 to the sum of the doping amounts of M2 and W is 1:(0.1 - 2), and optionally 1:(0.5 - 1.5).

[0045] When the ratio of the doping amount of M1 to the sum of the doping amounts of M2 and W is controlled within a predetermined range, it can be ensured that the high-nickel ternary cathode material has a relatively high capacity, and the structural stability of the material can be maximally enhanced, thereby further improving the cycle performance of the secondary battery.

[0046] Since the influence of the M1 element on the capacity reduction of the high-nickel ternary cathode material is relatively small, and the influence of the M2 and W elements on the capacity reduction is relatively large, when the ratio of the doping amount of M1 to the sum of the doping amounts of M2 and W is within the above range, the capacity of the secondary battery can be maintained or improved, and the cycle and storage performance of the secondary battery can be further enhanced.

[0047] In some embodiments, the thickness d of the surface layer satisfies 0 < d < 3 μm, and optionally 0 < d < 2 μm.

[0048] When the thickness d of the surface layer is within a predetermined range, the cycle performance of the battery can be further improved. Therefore, it is possible to avoid the situation where when the thickness d of the surface layer is too large, the matrix component changes greatly, reducing the Ni content in the entire matrix, thereby significantly reducing the capacity of the ternary cathode material.

[0049] In some embodiments, the sum of the surface doping amount of Co and the coating amount of the Co-containing compound is 100 - 20000 ppm, and optionally 1000 - 13000 ppm; the coating amount of the Al-containing compound is 100 - 3000 ppm, and optionally 500 - 2000 ppm; the coating amount of the B-containing compound is 100 - 2000 ppm, and optionally 500 - 1500 ppm. Here, both the surface doping amount and the coating amount are converted in terms of the corresponding element in the compound with respect to the modified high-nickel ternary cathode material.

[0050] When the sum of the surface doping amount of Co and the coating amount of Co-containing compound is within a certain range, the cycle performance of the battery can be further improved. Therefore, when the sum of the surface doping amount of Co and the coating amount of Co-containing compound is too large, the inactive Co compound remains excessively on the surface of the high nickel ternary positive electrode material, which may affect the capacity of the material and affect the cycle performance of the secondary battery.

[0051] When the coating amount of the Al-containing compound and the coating amount of the B-containing compound are within the predetermined range, the cycle performance of the battery can be further improved.

[0052] In some embodiments, the total thickness of the inner and outer coating layers is 0.001-1 μm.

[0053] In some embodiments, the coating amount of the Al-containing compound and the coating amount of the B-containing compound satisfy a weight ratio of Al to B of (0.5-2:1), where each of the coating amounts is calculated as the corresponding element in the compound for the modified high nickel ternary cathode material.

[0054] When the coating amount of the Al-containing compound and the coating amount of the B-containing compound satisfy a certain relationship, the capacity and cycle performance of the secondary battery can be further improved. Therefore, when the weight ratio of Al to B in the outer coating layer is greater than 2:1, the Al-containing compound has no activity, which can affect the ion transmission kinetic activity and further affect the capacity and cycle performance of the secondary battery.

[0055] In some embodiments, the doping amount of W is 100-2000 ppm, optionally 100-1500 ppm, the doping amount of M1 is 2000-4000 ppm, and the doping amount of M2 is 500-2000 ppm, all of which are calculated as the corresponding element for the modified high nickel ternary cathode material.

[0056] When the doping amounts of M1, M2 and W are within a certain range, the structural stability of the high nickel ternary positive electrode material can be further improved, thereby further improving the cycle performance and storage performance of the secondary battery.

[0057] In some embodiments, the sum of the surface doping amount of Co and the coating amount of the Co-containing compound, the Al-containing compound, and the B-containing compound is 1000-22000 ppm, optionally 1000-15000 ppm, where both the surface doping amount and the coating amount are calculated in terms of the corresponding element in the compound for the modified high nickel ternary cathode material.

[0058] In some embodiments, the volumetric particle size distribution diameter distance of the modified high nickel ternary cathode material is (Dv 90 -Dv 10 ) / Dv 50 ≧1.1, selectively (Dv 90 -Dv 10 ) / Dv 50 ≧ 1.2.

[0059] In this application, the particle volume distribution particle size Dv of the modified high nickel ternary positive electrode material 10 , D.V. 50 , D.V. 90 is a well-known concept in the art. 10 Dv is the particle size that reaches 10% of the total volume from the small particle size side in the particle size distribution based on volume of powder particles, and is generally expressed in μm. 50 Dv is the particle size that reaches 50% of the total volume of the powder particles from the small particle size side in the particle size distribution based on volume. 90 is the particle size at which the cumulative volume of the powder particles reaches 90% from the small particle size side in the particle size distribution based on volume. 10 , D.V. 50 , D.V. 90The test method can be tested using methods known in the art. As an example, referring to the GB / T 19077-2016 / ISO 13320:2009 laser diffraction method for particle size distribution, it can be measured using a Mastersizer 2000 instrument.

[0060] In some embodiments, the modified high-nickel ternary cathode material has a powder compaction density of ≧3.4 g / cc at a pressure of 5 tons, and optionally ≧3.5 g / cc.

[0061] When the modified high-nickel ternary cathode material has a wide volume particle size distribution diameter distance and a relatively high powder compaction density, the volume energy density of the high-nickel ternary cathode material can be significantly increased.

[0062] This application further provides a method for manufacturing a modified high-nickel ternary cathode material. Mixing a lithium salt, a high-nickel ternary precursor doped with W, a compound containing M1, and a compound containing M2, and sintering to obtain a high-nickel ternary cathode material substrate doped with M1, M2, and W, wherein the chemical formula of the high-nickel ternary precursor doped with W is (Ni X Co Y Mn Z W D )(OH) 2 where 0.65 ≦ X < 1, 0 ≦ Y < 0.3, 0 ≦ Z < 0.3, 0 < D < 0.1, M1 is one of Mo, Zr, Ti, Sb, Nb, Te, M2 is one of Mg, Al, Ca, Zn, Sr, and the chemical formula of the high-nickel ternary cathode material substrate doped with M1, M2, and W is Li 1+a [Ni x Co y Mn z M1 b M2 c W d O 2where 0.65 ≤ x < 1, 0 ≤ y < 0.3, 0 ≤ z < 0.3, 0 < a < 0.2, 0 < b < 0.1, 0 < c < 0.1, 0 < d < 0.1, x + y + z + b + c + d = 1, and optionally 0.8 ≤ x < 1, step S1, Mixing the high nickel ternary cathode material substrate doped with M1, M2, and W with a Co-containing compound and sintering to obtain a high nickel ternary cathode material in which Co is doped in the surface layer and the surface is coated with a Co-containing compound, step S2, Including step S3 of mixing and sintering the high nickel ternary cathode material in which Co is doped in the surface layer and the surface is coated with a Co-containing compound, an Al-containing compound, and a B-containing compound to obtain a modified high nickel ternary cathode material.

[0063] In some embodiments, in step S1, the sintering temperature is 700 - 950 °C, the sintering time is 10 - 20 h, and the sintering atmosphere is air or O 2 is.

[0064] By adopting the sintering process in step S1, a high nickel ternary cathode material substrate with excellent crystal structure can be obtained, and the co-doping of the three elements (i.e., M1, M2, W) can be carried out uniformly and effectively. Especially when the sintering temperature in step S1 is within an appropriate temperature range, the capacity, cycle performance, and storage performance of the secondary battery can be further improved.

[0065] In the examples of this application, the types of lithium salts, compounds containing M1, and compounds containing M2 are not particularly limited and can be selected according to actual needs. For example, the lithium salt is lithium hydroxide, lithium carbonate, or lithium nitrate, and the compounds containing M1 and M2 are oxides or carbonates of M1 and M2.

[0066] In the examples of this application, the synthesis method of the high nickel ternary precursor doped with W includes the following steps.

[0067] (1): A nickel-cobalt-manganese mixed metal salt solution is prepared using a nickel salt, a cobalt salt, a manganese salt and pure water, and a tungsten-containing compound is added to obtain a nickel-cobalt-manganese mixed metal salt solution doped with W salt; (2): Add pure water to the reaction vessel to prepare a base solution, start stirring to maintain the reaction temperature, add an alkaline solution and an aqueous ammonia solution to adjust the pH value and ammonia concentration of the base solution, add the nickel-cobalt-manganese mixed metal salt solution doped with the W salt, an alkaline solution, and an aqueous ammonia solution to the reaction vessel, and maintain the pH value and ammonia concentration constant to synthesize a seed crystal nucleus slurry; (3): Add pure water to the reaction vessel to prepare a base solution, add the seed crystal nucleus slurry, start stirring to maintain the reaction temperature, add an alkaline solution and an aqueous ammonia solution to adjust the pH value and ammonia concentration of the base solution, add the W salt-doped nickel-cobalt-manganese mixed metal salt solution, an alkaline solution, an aqueous ammonia solution and the seed crystal nucleus slurry to the reaction vessel, maintain the pH value and ammonia concentration constant, and obtain a W-doped high-nickel ternary precursor.

[0068] In some embodiments, in step (1), the concentration of the nickel-cobalt-manganese mixed metal salt solution is 0.5-2.5 mol / L.

[0069] In the embodiment of the present application, the types of nickel salt, cobalt salt, manganese salt and tungsten-containing compound are not particularly limited and can be selected according to actual needs.For example, the nickel salt is one of nickel nitrate, nickel acetate and nickel sulfate, the cobalt salt is one of cobalt nitrate, cobalt acetate and cobalt sulfate, the manganese salt is one of manganese nitrate, manganese acetate and manganese sulfate, and the tungsten-containing compound is sodium tungstate.

[0070] In some embodiments, the added deionized water in steps (2) and (3) occupies 10-50% of the reaction kettle volume.

[0071] In some embodiments, in steps (2) and (3), the alkaline solution is a sodium hydroxide solution, and the concentration is 1-10 mol / L.

[0072] In some embodiments, in steps (2) and (3), the concentration of the aqueous ammonia solution is 2-14 mol / L.

[0073] In some embodiments, in step (2), the pH is 11.5-12.5, optionally 11.8-12.2, the ammonia concentration is 0.2-0.6 mol / L, optionally 0.3-0.5 mol / L, the linear stirring velocity is 5.0-7.0 m / s, and the reaction temperature is 40-75° C.

[0074] In some embodiments, in step (2), the flow ratio of the W-salt-doped nickel-cobalt-manganese mixed metal salt solution, the alkaline solution, and the aqueous ammonia solution is 18.75:15:1.

[0075] In some embodiments, in step (3), the pH is 11.0-12.0, optionally 11.1-11.7, the ammonia concentration is 0.2-0.6 mol / L, optionally 0.3-0.5 mol / L, the linear stirring velocity is 3.0-6.0 m / s, and the reaction temperature is 40-75° C.

[0076] In some embodiments, in step (3), the flow ratio of the W-salt-doped nickel-cobalt-manganese mixed metal salt solution, the alkaline solution, the ammonia aqueous solution and the seed crystal nucleus slurry is 18.75:15:1:2.8.

[0077] In some embodiments, the seed nucleus slurry has a volume distribution average particle size Dv 50 is 1-5 μm, and the volume distribution average particle size Dv 50 is 5-15 μm, and optionally 5-10 μm.

[0078] In some embodiments, the W-doped high nickel ternary precursor has a volumetric particle size distribution diameter distance (Dv 90 -Dv 10 ) / Dv 50 ≧1.3.

[0079] The bulk phase structure of the W-doped high-nickel ternary precursor synthesized by this method is uniformly doped with W element and has a wide volumetric grain size distribution diameter distance, so that the sintered high-nickel ternary positive electrode material has a wide grain size distribution and a relatively high powder compaction density.

[0080] In some embodiments, in step S2, the Co-containing compound is Co 3 O 4 , Co(OH) 2 , CoO, CoOOH, Cobalt acetate, Cobalt oxalate, CoCO 3 One or more of the following.

[0081] In some embodiments, in step S2, the particle size of the Co-containing compound is 0.001-10 μm, optionally 0.001-1 μm.

[0082] When the particle size of the Co-containing compound is within a certain range, it can be uniformly coated on the surface of the high-nickel ternary positive electrode material, and can improve the interfacial side reaction between the material and the electrolyte, thereby further improving the cycle performance of the secondary battery.

[0083] In some embodiments, in step S2, the sintering temperature is 500-800° C., optionally 550-750° C., the sintering time is 5-15 h, optionally 5-10 h, and the sintering atmosphere is air or O. 2 It is.

[0084] By controlling the sintering temperature in step S2, the Co-containing compound can react with the lithium impurities on the surface of the ternary positive electrode material, and the Co-containing compound can be tightly coated on the surface of the ternary positive electrode material, thereby reducing the lithium impurities on the surface, improving the interfacial side reactions, and further improving the cycle performance of the secondary battery.

[0085] In some embodiments, in step S3, the Al-containing compound is Al 2 O 3 , Al(OH) 3 , Al 2 (SO 4 ) 3 , AlCl 3 , Al(NO) 3 One or more of the following:

[0086] In some embodiments, in step S3, the B-containing compound is BCl 3 , B 2 (SO 4 ) 3 , B(NO 3 ) 3 , BN, B 2 O 3 , B.F. 3 , BBr 3 , B.I. 3 , H 2 BO 5 P, H 3 BO 3 , C 5 H 6 B(OH) 2 , C 3 H 9 B 3 O 6 , (C 2 H 5 O) 3 B and (C 3 H 7 O) 3 B is one or more.

[0087] In some embodiments, in step S3, the sintering temperature is 200-500° C., optionally 200-400° C., the sintering time is 5-15 h, optionally 5-10 h, and the sintering atmosphere is air or O. 2 It is.

[0088] By controlling the sintering temperature in step S3, the Al-containing compound and the B-containing compound can be tightly coated on the surface of the ternary positive electrode material, thereby improving the interfacial reaction of the materials and further improving the cycle performance of the secondary battery.

[0089] In addition, the secondary battery, the battery module, the battery pack and the power consuming device of the present application will be described below with appropriate reference to the drawings.

[0090] In one embodiment of the present application, a secondary battery is provided.

[0091] Generally, a secondary battery includes a positive electrode plate, a negative electrode plate, an electrolyte, and a separator. During charging and discharging of the battery, active ions are absorbed and released by shuttle between the positive electrode plate and the negative electrode plate. The electrolyte serves to conduct ions between the positive electrode plate and the negative electrode plate. The separator is installed between the positive electrode plate and the negative electrode plate, and serves mainly to prevent short circuit between the positive and negative electrodes, while allowing ions to pass through.

[0092] [Positive electrode plate] The positive electrode plate includes a positive current collector and a positive film layer disposed on at least one surface of the positive current collector, the positive film layer including the modified high nickel ternary positive electrode material of the first aspect of the present application.

[0093] For example, the positive electrode current collector has two opposing surfaces in the thickness direction of the positive electrode current collector, and the positive electrode film layer is disposed on either one or both of the two opposing surfaces of the positive electrode current collector.

[0094] In some embodiments, the positive electrode current collector may be a metal foil sheet or a composite current collector. For example, the metal foil sheet may be an aluminum foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base layer. The composite current collector may be formed by forming a metal material (such as aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0095] In some embodiments, the positive electrode membrane layer optionally further comprises an adhesive, which may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylic ester resin.

[0096] In some embodiments, the positive electrode membrane layer optionally further comprises a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers, by way of example.

[0097] In some embodiments, the positive electrode plate may be manufactured in the following manner: Components for manufacturing the positive electrode plate, such as a positive electrode active material, a conductive agent, an adhesive, and any other components, are dispersed in a solvent (e.g., N-methylpyrrolidone) to form a positive electrode slurry, and the positive electrode slurry is applied onto a positive electrode current collector, followed by processes such as drying and cold pressing to obtain a positive electrode plate.

[0098] [Negative electrode plate] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, the negative electrode film layer including a negative electrode active material.

[0099] For example, the negative electrode current collector has two opposing surfaces in the thickness direction of the negative electrode current collector, and the negative electrode film layer is disposed on either one or both of the two opposing surfaces of the negative electrode current collector.

[0100] In some embodiments, the negative electrode current collector may be a metal foil sheet or a composite current collector. For example, the metal foil sheet may be a copper foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base. The composite current collector may be formed by forming a metal material (such as copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0101] In some embodiments, the negative electrode active material may be a battery negative electrode active material known in the art. For example, the negative electrode active material may include at least one of artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based material, tin-based material, and lithium titanate. The silicon-based material may be selected from at least one of silicon elemental, silicon oxide compound, silicon carbon composite, silicon nitrogen composite, and silicon alloy. The tin-based material may be selected from at least one of tin elemental, stannate compound, and tin alloy. However, the present application is not limited to these materials, and other conventional materials that can be used as a battery negative electrode active material may be used. These negative electrode active materials may be used alone or in combination of two or more.

[0102] In some embodiments, the negative electrode membrane layer optionally further comprises an adhesive, which may be selected from at least one of styrene butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0103] In some embodiments, the negative electrode film layer optionally further comprises a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0104] In some embodiments, the negative electrode membrane layer optionally further comprises other auxiliary agents, such as a thickening agent (eg, sodium carboxymethylcellulose (CMC-Na)).

[0105] In some embodiments, the negative electrode plate may be manufactured in the following manner: The above-mentioned components for manufacturing the negative electrode plate, such as the negative electrode active material, the conductive agent, the adhesive, and any other components, are dispersed in a solvent (e.g., deionized water) to form a negative electrode slurry, and the negative electrode slurry is applied onto a negative electrode current collector, and the negative electrode plate is obtained after processes such as drying and cold pressing.

[0106] [Electrolytes] The electrolyte serves to conduct ions between the positive and negative electrodes. The present application is not specifically limited to the type of electrolyte, and may be selected according to need. For example, the electrolyte may be liquid, gel, or all solid.

[0107] In some embodiments, the electrolyte is an electrolytic solution, the electrolytic solution including an electrolyte salt and a solvent.

[0108] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, bisfluorosulfonylimide, lithium bistrifluoromethanesulfonylimide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium bis(oxalato)borate, lithium difluorobis(oxalato)phosphate, and lithium tetrafluoro(oxalato)phosphate.

[0109] In some embodiments, the solvent may be selected from at least one of ethylene carbonate (EC), propylene carbonate, ethyl methyl carbonate, diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone lactone, sulfolane, dimethyl sulfone, ethyl methyl sulfone, and diethyl sulfone.

[0110] In some embodiments, the electrolyte solution may further include optional additives. For example, the additives may include an anode film-forming additive and a cathode film-forming additive, and may further include additives that can improve some performance of the battery, such as an additive that improves the battery overcharge performance, an additive that improves the battery's high temperature or low temperature performance, etc.

[0111] [Separator] In some embodiments, the secondary battery further includes a separator. The present application is not particularly limited to the type of separator, and any known porous structure separator having good chemical stability and mechanical stability may be selected.

[0112] In some embodiments, the material of the separator may be at least one selected from glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single layer film or a multi-layer composite film, and is not particularly limited. When the separator is a multi-layer composite film, the materials of each layer may be the same or different, and is not particularly limited.

[0113] In some embodiments, the positive and negative plates and the separator may be fabricated into an electrode assembly by a winding or lamination process.

[0114] In some embodiments, the secondary battery may include an exterior body, which may be used to package the electrode assembly and the electrolyte.

[0115] In some embodiments, the exterior of the secondary battery may be a hard case, such as a hard plastic case, an aluminum case, a steel case, etc. The exterior of the secondary battery may be a pouch, such as a pouch-shaped pouch. The material of the pouch may be plastic, such as polypropylene, polybutylene terephthalate, polybutylene terephthalate, polybutylene succinate, etc.

[0116] The present application is not particularly limited to the shape of the secondary battery, which may be cylindrical, rectangular or any other shape. For example, FIG. 5 shows a secondary battery 5 with a rectangular structure as an example.

[0117] In some embodiments, referring to FIG. 6, the exterior body may include a case 51 and a cover plate 53. Here, the case 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate surround and form a receiving cavity. The case 51 may have an opening communicating with the receiving cavity, and the cover plate 53 may be disposed over the opening to seal the receiving cavity. The positive electrode plate, the negative electrode plate and the separator may be wound or stacked to form an electrode assembly 52. ​​The electrode assembly 52 is packaged in the receiving cavity. An electrolyte is permeated into the electrode assembly 52. ​​The number of electrode assemblies 52 included in the secondary battery 5 may be one or more, and may be selected by those skilled in the art according to specific actual needs.

[0118] In some embodiments, the secondary batteries may be assembled into a battery module, and the number of secondary batteries included in the battery module may be one or more, with the specific number being selectable by one skilled in the art depending on the application and capacity of the battery module.

[0119] Fig. 7 shows an example of a battery module 4. Referring to Fig. 7, a plurality of secondary batteries 5 may be arranged in order along the longitudinal direction of the battery module 4 in the battery module 4. Of course, they may be arranged in any other manner. Furthermore, the plurality of secondary batteries 5 may be fixed by fasteners.

[0120] Optionally, the battery module 4 may further include a housing having an accommodating space, and the multiple secondary batteries 5 are accommodated in the accommodating space.

[0121] In some embodiments, the battery modules may be assembled into a battery pack, and the battery pack may include one or more battery modules, the specific number of which may be selected by one skilled in the art depending on the application and capacity of the battery pack.

[0122] 8 and 9 show an example of a battery pack 1. Referring to Fig. 8 and Fig. 9, the battery pack 1 may include a battery box and a plurality of battery modules 4 installed in the battery box. The battery box may include an upper housing 2 and a lower housing 3, and the upper housing 2 is covered by the lower housing 3 to form a sealed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.

[0123] The present application further provides a power consuming device, the power consuming device including one or more of the secondary batteries, battery modules, or battery packs according to the present application. The secondary batteries, battery modules, or battery packs may be used as a power source for the power consuming device, or may be used as an energy storage unit for the power consuming device. The power consuming device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships, satellites, energy storage systems, etc.

[0124] The power consumption device may be a secondary battery, a battery module, or a battery pack, depending on the usage needs.

[0125] 10 shows an example power consumption device, such as a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. A battery pack or battery module may be employed to meet the demand for high power and high energy density of the secondary battery of the power consumption device.

[0126] As another example, the power consuming device may be a mobile phone, a tablet computer, a notebook computer, etc. This power consuming device is generally required to be thin, and may employ a secondary battery as a power source.

[0127] Working Example The following describes the examples of the present application. The examples described below are illustrative and are only used to interpret the present application, and should not be understood as limitations to the present application. If no specific techniques or conditions are specified in the examples, they will be performed according to the techniques or conditions described in the literature in the field, or according to the product specifications. If no manufacturer is specified, the reagents or instruments used are all ordinary products that can be purchased commercially.

[0128] Example 1-1 [Preparation of tungsten-doped high-nickel ternary precursor] (1): Using nickel sulfate, cobalt sulfate, manganese sulfate and pure water, a nickel-cobalt-manganese mixed metal salt solution was prepared with nickel, cobalt and manganese in a molar ratio of 90:5:5 and a concentration of 2 mol / L, and sodium tungstate was added to the solution in an amount of 1000 ppm in terms of tungsten to obtain a nickel-cobalt-manganese mixed metal salt solution doped with tungsten salt; (2): 20L of pure water is added to a 100L reactor, stirring is started, the stirring speed is 6m / s, and the temperature is kept constant at 45℃. 5mol / L of NaOH solution is added until the pH of the reactor reaches 12.0, and 9mol / L of aqueous ammonia solution is added until the ammonia concentration of the reactor reaches 0.4mol / L. The tungsten salt-doped nickel-cobalt-manganese mixed metal salt solution, NaOH solution, and aqueous ammonia solution are added to the reactor, where the flow ratio of the tungsten salt-doped nickel-cobalt-manganese mixed metal salt solution and NaOH solution is 5:4, and the flow ratio of the NaOH solution and aqueous ammonia solution is 15:1, thereby maintaining the ammonia concentration and pH in the reactor constant, and continuously reacting to synthesize a seed crystal nucleus slurry; (3): Add 20L of pure water into another 100L reactor, add 2kg of the seed crystal nucleus slurry, start stirring, the stirring speed is 5m / s, and maintain a constant temperature of 50℃. Add 5mol / L NaOH solution until the pH of the reactor becomes 11.5, and add 9mol / L ammonia aqueous solution until the ammonia concentration of the reactor becomes 0.3mol / L. The tungsten salt-doped nickel-cobalt-manganese mixed metal salt solution, NaOH solution, ammonia aqueous solution and the seed crystal nucleus slurry were added to a reaction vessel, where the flow ratio of the tungsten salt-doped nickel-cobalt-manganese mixed metal salt solution and NaOH solution was 5:4, the flow ratio of the NaOH solution and ammonia aqueous solution was 15:1, and the flow ratio of the seed crystal nucleus slurry and the tungsten salt-doped nickel-cobalt-manganese mixed metal salt solution was 0.15, thereby maintaining the ammonia concentration and pH in the reaction vessel constant, and reacting continuously to synthesize a slurry tungsten-doped high nickel ternary precursor. Then, the slurry was centrifuged at 300 rpm for 20 min, washed with deionized water, filtered and dried at 105 ° C for 10 h to obtain a tungsten-doped high nickel ternary precursor, whose molecular formula is (Ni 0.8995 Co 0.05 Mn 0.05 W 0.0005 )(OH) 2 and the grain size Dv 50 is 8 μm, and the particle size volume distribution diameter distance (D v90 -D v10 ) / D v50 is 1.35.

[0129] [Preparation of modified high-nickel ternary positive electrode materials] S1: Lithium hydride, the tungsten doped high nickel ternary precursor, and TiO 2 And, Al 2 O 3 and mixed in a Proshare mixer, where the molar ratio of Li to the sum of the three components of nickel, cobalt, and manganese is 1.05, and TiO 2 The amount of Ti is 2500 ppm, and Al is 2 O 3The amount of Al was 1000 ppm, and the mixture was sintered in a kiln. The sintering temperature was 750°C, the sintering time was 15 h, and the sintering atmosphere was O 2 A high-nickel ternary positive electrode material substrate doped with Ti, Al and W was obtained, whose molecular formula is Li 1.05 [Ni 0.8918 Co 0.0495 Mn 0.0495 Ti 0.005 Al 0.0037 W 0.0005 ]O 2 and S2: The Ti, Al and W doped high nickel ternary positive electrode material substrate and CoO are mixed in a Proshare mixer, where the amount of CoO is 13000 ppm in terms of Co. The mixture is sintered in a kiln at a sintering temperature of 600° C. for 5 h in an O 2 atmosphere. 2 and obtaining a high-nickel ternary positive electrode material in which the surface layer is doped with Co and the surface is coated with a Co-containing compound; S3: A high-nickel ternary positive electrode material in which the surface layer is doped with Co and the surface is coated with a Co-containing compound, and Al 2 O 3 , B 2 O 3 and mixed in a Proshare mixer, where Al 2 O 3 The amount of Al is 1000 ppm, and B 2 O 3 The amount of Al was 1000 ppm in terms of B, and the weight ratio of Al to B was 1:1. The mixture was sintered in a kiln at a sintering temperature of 250°C for 6 hours in an O 2 A modified high-nickel ternary positive electrode material product is obtained, and the total thickness of the inner and outer coating layers of the product is 0.54 μm.

[0130] Example 1-2 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in the preparation of the tungsten-doped high-nickel ternary precursor, the molar ratio of nickel, cobalt, and manganese in the nickel-cobalt-manganese mixed metal salt solution is 80:10:10, and the molecular formula of the obtained tungsten-doped high-nickel ternary precursor is (Ni 0.7996 Co 0.09995 Mn 0.09995 W 0.0005 )(OH) 2 In the preparation of the modified high-nickel ternary positive electrode material, in step S1, a high-nickel ternary positive electrode material substrate doped with Ti, Al and W is obtained, the molecular formula of which is Li 1.05 [Ni 0.7927 Co 0.0991 Mn 0.0991 Ti 0.005 Al 0.0036 W 0.0005 ]O 2 It is.

[0131] Examples 1-3 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in the preparation of the tungsten-doped high-nickel ternary precursor, the molar ratio of nickel, cobalt, and manganese in the nickel-cobalt-manganese mixed metal salt solution is 70:15:15, and the molecular formula of the obtained tungsten-doped high-nickel ternary precursor is (Ni 0.6997 Co 0.1499 Mn 0.1499 W 0.0005 )(OH) 2 In the preparation of the modified high-nickel ternary positive electrode material, in step S1, a high-nickel ternary positive electrode material substrate doped with Ti, Al and W is obtained, the molecular formula of which is Li 1.05 [Ni 0.6936 Co 0.1486 Mn 0.1486 Ti 0.005 Al 0.0037 W 0.0005 ]O 2 It is.

[0132] Comparative Example 1-1 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in the preparation of the modified high-nickel ternary positive electrode material, in step S1, TiO 2 Without adding any additives, a high-nickel ternary positive electrode material substrate doped with Al and W was obtained, whose molecular formula is Li 1.05 [Ni 0.8963 Co 0.0498 Mn 0.0498 Al 0.0036 W 0.0005 ]O 2 It is.

[0133] Comparative Example 1-2 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in the preparation of the modified high-nickel ternary positive electrode material, in step S1, Al 2 O 3 Without adding any nickel, a high-nickel ternary positive electrode material substrate doped with Ti and W was obtained, the molecular formula of which is Li 1.05 [Ni 0.895 Co 0.0497 Mn 0.0497 Ti 0.0051 W 0.0005 ]O 2 It is.

[0134] Comparative Example 1-3 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in the preparation of the tungsten-doped high-nickel ternary precursor, no sodium tungstate is added, and the molecular formula of the obtained high-nickel ternary precursor is (Ni 0.90 Co 0.05 Mn 0.05 )(OH) 2 In the preparation of the modified high-nickel ternary positive electrode material, in step S1, a high-nickel ternary positive electrode material substrate doped with Ti and Al is obtained, the molecular formula of which is Li 1.05 [Ni 0.8923 Co 0.0496 Mn 0.0496 Ti 0.005 Al 0.0035 ]O 2It is.

[0135] Comparative Example 1-4 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that step S2 is not performed, and the total thickness of the inner and outer coating layers of the final product is 0.11 μm.

[0136] Comparative Examples 1-5 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that step S3 is not performed, and the total thickness of the inner and outer coating layers of the final product is 0.40 μm.

[0137] Comparative Examples 1-6 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in step S3, B 2 O 3 No coating is added, and the total thickness of the inner and outer coating layers of the final product is 0.49 μm.

[0138] Comparative Example 1-7 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in step S3, Al 2 O 3 No coating is added, and the total thickness of the inner and outer coating layers of the final product is 0.50 μm.

[0139] Example 2-1 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in the preparation of the modified high-nickel ternary positive electrode material, in step S1, TiO 2 ZrO 2 Replace with Al 2 O 3 SrCO 3 To obtain a high-nickel ternary positive electrode material substrate doped with Zr, Sr and W, the molecular formula of which is Li 1.05 [Ni 0.8961 Co 0.0498 Mn 0.0498 Zr 0.0027 Sr0.0011 W 0.0005 ]O 2 It is.

[0140] Example 2-2 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in the preparation of the modified high-nickel ternary positive electrode material, in step S1, TiO 2 Sb 2 O 5 Replace with Al 2 O 3 was replaced with MgO to obtain a high nickel ternary cathode material substrate doped with Sb, Mg and W, the molecular formula of which is Li 1.05 [Ni 0.8941 Co 0.0497 Mn 0.0497 Sb 0.002 Mg 0.004 W 0.0005 ]O 2 It is.

[0141] Example 2-3 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in the preparation of the modified high-nickel ternary positive electrode material, in step S1, Al 2 O 3 was replaced with ZnO to obtain a high-nickel ternary positive electrode material substrate doped with Ti, Zn and W, the molecular formula of which is Li 1.05 [Ni 0.8937 Co 0.0496 Mn 0.0496 Ti 0.005 Zinc 0.0016 W 0.0005 ]O 2 It is.

[0142] Example 3-1 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in the preparation of the tungsten-doped high-nickel ternary precursor, the amount of sodium tungstate added is 2000 ppm in terms of tungsten, and the molecular formula of the obtained tungsten-doped high-nickel ternary precursor is (Ni 0.8991Co 0.04995 Mn 0.04995 W 0.001 )(OH) 2 In the preparation of the modified high-nickel ternary positive electrode material, in step S1, TiO 2 The amount of Ti is 2000 ppm, and Al is 2 O 3 The amount of Al was 2000 ppm, and a high-nickel ternary positive electrode material substrate doped with Ti, Al and W was obtained, and its molecular formula was Li 1.05 [Ni 0.889 Co 0.0494 Mn 0.0494 Ti 0.004 Al 0.0072 W 0.001 ]O 2 It is.

[0143] Example 3-2 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, but the difference is that in the preparation of the tungsten-doped high-nickel ternary precursor, the amount of sodium tungstate added is 1500 ppm in terms of tungsten, and the molecular formula of the obtained tungsten-doped high-nickel ternary precursor is (Ni 0.8992 Co 0.05 Mn 0.05 W 0.0008 )(OH) 2 In the preparation of the modified high-nickel ternary positive electrode material, in step S1, TiO 2 The amount of Ti is 2000 ppm, and Al is 2 O 3 The amount of Al was 1500 ppm, and a high-nickel ternary positive electrode material substrate doped with Ti, Al and W was obtained, and its molecular formula was Li 1.05 [Ni 0.8909 Co 0.0495 Mn 0.0495 Ti 0.004 Al 0.0053 W 0.0008 ]O 2 It is.

[0144] Example 3-3 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, but the difference is that in the preparation of the tungsten-doped high-nickel ternary precursor, the amount of sodium tungstate added is 100 ppm in terms of tungsten, and the molecular formula of the obtained tungsten-doped high-nickel ternary precursor is (Ni 0.8999 Co 0.05 Mn 0.05 W 0.0001 )(OH) 2 In the preparation of the modified high-nickel ternary positive electrode material, in step S1, TiO 2 The amount of Ti is 2000 ppm, and Al is 2 O 3 The amount of Al was 1900 ppm, and a high-nickel ternary positive electrode material substrate doped with Ti, Al and W was obtained, and its molecular formula was Li 1.05 [Ni 0.8901 Co 0.0495 Mn 0.0495 Ti 0.004 Al 0.0068 W 0.0001 ]O 2 It is.

[0145] Examples 3-4 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, but the difference is that in the preparation of the tungsten-doped high-nickel ternary precursor, the amount of sodium tungstate added is 500 ppm in terms of tungsten, and the molecular formula of the obtained tungsten-doped high-nickel ternary precursor is (Ni 0.8997 Co 0.05 Mn 0.05 W 0.0003 )(OH) 2 In the preparation of the modified high-nickel ternary positive electrode material, in step S1, TiO 2 The amount of Ti is 3000 ppm, and Al is 2 O 3 The amount of Al was 1000 ppm, and a high-nickel ternary positive electrode material substrate doped with Ti, Al and W was obtained, and its molecular formula was Li 1.05 [Ni 0.8911 Co 0.0495Mn 0.0495 Ti 0.006 Al 0.0036 W 0.0003 ]O 2 It is.

[0146] Examples 3-5 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in the preparation of the tungsten-doped high-nickel ternary precursor, the amount of sodium tungstate added is 1900 ppm in terms of tungsten, and the molecular formula of the obtained tungsten-doped high-nickel ternary precursor is (Ni 0.899 Co 0.05 Mn 0.05 W 0.001 )(OH) 2 In the preparation of the modified high-nickel ternary positive electrode material, in step S1, TiO 2 The amount of Ti is 4000 ppm, and Al is 2 O 3 The amount of Al was 500 ppm, and a high-nickel ternary positive electrode material substrate doped with Ti, Al and W was obtained, and its molecular formula was Li 1.05 [Ni 0.8902 Co 0.0495 Mn 0.0495 Ti 0.008 Al 0.0018 W 0.001 ]O 2 It is.

[0147] Examples 3-6 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, but the difference is that in the preparation of the tungsten-doped high-nickel ternary precursor, the amount of sodium tungstate added is 100 ppm in terms of tungsten, and the molecular formula of the obtained tungsten-doped high-nickel ternary precursor is (Ni 0.8999 Co 0.05 Mn 0.05 W 0.0001 )(OH) 2 In the preparation of the modified high-nickel ternary positive electrode material, in step S1, TiO 2The amount of Ti is 6000 ppm, and Al is 2 O 3 The amount of Al was 500 ppm, and a high-nickel ternary positive electrode material substrate doped with Ti, Al and W was obtained, and its molecular formula was Li 1.05 [Ni 0.8875 Co 0.0493 Mn 0.0493 Ti 0.012 Al 0.0018 W 0.0001 ]O 2 It is.

[0148] Examples 3-7 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, but the difference is that in the preparation of the tungsten-doped high-nickel ternary precursor, the amount of sodium tungstate added is 100 ppm in terms of tungsten, and the molecular formula of the obtained tungsten-doped high-nickel ternary precursor is (Ni 0.8999 Co 0.05 Mn 0.05 W 0.0001 )(OH) 2 In the preparation of the modified high-nickel ternary positive electrode material, in step S1, TiO 2 The amount of Ti is 4000 ppm, and Al is 2 O 3 The amount of Ti, Al and W was 100 ppm, and a high-nickel ternary positive electrode material substrate doped with Ti, Al and W was obtained, and its molecular formula was Li 1.05 [Ni 0.8923 Co 0.0496 Mn 0.0496 Ti 0.008 Al 0.0004 W 0.0001 ]O 2 It is.

[0149] Examples 3-8 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, but the difference is that in the preparation of the tungsten-doped high-nickel ternary precursor, the amount of sodium tungstate added is 3000 ppm in terms of tungsten, and the molecular formula of the obtained tungsten-doped high-nickel ternary precursor is (Ni 0.8984 Co 0.05 Mn 0.05 W 0.0016 )(OH) 2 In the preparation of the modified high-nickel ternary positive electrode material, in step S1, TiO 2 The amount of Ti is 2000 ppm, and Al is 2 O 3 The amount of Al was 3000 ppm, and a high-nickel ternary positive electrode material substrate doped with Ti, Al and W was obtained, and its molecular formula was Li 1.05 [Ni 0.8854 Co 0.0492 Mn 0.0492 Ti 0.004 Al 0.0106 W 0.0016 ]O 2 It is.

[0150] Example 4-1 The preparation of the modified high nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in step S2, the amount of CoO is 20000 ppm in terms of Co, and the total thickness of the inner and outer coating layers of the final product is 1.0 μm.

[0151] Example 4-2 The preparation of the modified high nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in step S2, the amount of CoO is 5000 ppm in terms of Co, and the total thickness of the inner and outer coating layers of the final product is 0.32 μm.

[0152] Example 4-3 The preparation of the modified high nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in step S2, the amount of CoO is 1000 ppm in terms of Co, and the total thickness of the inner and outer coating layers of the final product is 0.18 μm.

[0153] Example 4-4 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in step S2, the amount of CoO is 100 ppm in terms of Co, and the total thickness of the inner and outer coating layers of the final product is 0.13 μm.

[0154] Examples 4-5 The preparation of the modified high nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in step S2, the amount of CoO is 25000 ppm in terms of Co, and the total thickness of the inner and outer coating layers of the final product is 1.26 μm.

[0155] Examples 4-6 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in step S3, Al 2 O 3 The amount of Al is 3000 ppm, and B 2 O 3 The amount of Al was 2000 ppm in terms of B, the weight ratio of Al to B was 1.5:1, and the total thickness of the inner and outer coating layers of the final product was 0.60 μm.

[0156] Examples 4-7 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in step S3, Al 2 O 3 The amount of Al is 2000 ppm, and B 2 O 3 The amount of Al was 1000 ppm in terms of B, the weight ratio of Al to B was 2:1, and the total thickness of the inner and outer coating layers of the final product was 0.58 μm.

[0157] Examples 4-8 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in step S3, Al 2 O 3 The amount of Al is 500 ppm, and B 2 O 3 The amount of Al was 500 ppm in terms of B, the weight ratio of Al to B was 1:1, and the total thickness of the inner and outer coating layers of the final product was 0.51 μm.

[0158] Examples 4-9 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in step S3, Al 2 O 3 The amount of Al is 750 ppm, and B 2 O 3 The amount of Al is 1500 ppm in terms of B, the weight ratio of Al to B is 0.5:1, and the total thickness of the inner and outer coating layers of the final product is 0.55 μm.

[0159] Examples 4-10 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in step S3, Al 2 O 3 The amount of Al is 100 ppm, and B 2 O 3 The amount of Al was 100 ppm in terms of B, the weight ratio of Al to B was 1:1, and the total thickness of the inner and outer coating layers of the final product was 0.46 μm.

[0160] Example 4-11 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in step S3, Al 2 O 3 The amount of Al is 3000 ppm, and B 2 O 3 The amount of Al was 1000 ppm in terms of B, the weight ratio of Al to B was 3:1, and the total thickness of the inner and outer coating layers of the final product was 0.61 μm.

[0161] Example 4-12 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in step S2, the amount of CoO is 800 ppm in terms of Co, and in step S3, Al 2 O 3 The amount of Al is 100 ppm, and B 2 O 3 The amount of Al is 100 ppm in terms of B, the weight ratio of Al to B is 1:1, and the total thickness of the inner and outer coating layers of the final product is 0.13 μm.

[0162] Example 5-1 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in step S1, the sintering temperature is 700°C.

[0163] Example 5-2 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in step S1, the sintering temperature is 950°C.

[0164] Comparative Example 5-1 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in step S1, the sintering temperature is 650°C.

[0165] Comparative Example 5-2 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in step S1, the sintering temperature is 1000°C.

[0166] Example 6-1 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in step S2, the sintering temperature is 500°C.

[0167] Example 6-2 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in step S2, the sintering temperature is 550°C.

[0168] Example 6-3 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in step S2, the sintering temperature is 700°C.

[0169] Example 6-4 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in step S2, the sintering temperature is 800°C.

[0170] Comparative Example 6-1 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in step S2, the sintering temperature is 400°C.

[0171] Comparative Example 6-2 The preparation of the modified high-nickel ternary positive electrode material generally refers to Example 1-1, with the difference being that in step S2, the sintering temperature is 900°C.

[0172] Test Method 1. Measurement of W-doped high-nickel ternary precursor and M1, M2 and W-doped high-nickel ternary cathode material substrates We used an inductively coupled plasma optical emission spectrometer (ICP-OES), model number ICAP7400 manufactured by Thermo Fisher Scientific, USA. First, 1 g of sample was weighed into a beaker and added to the sample with 25% by volume of HNO 3 25ml of solution was added to dissolve the sample, diluted with 475ml of deionized water, and the diluted solution was put into the instrument for target element analysis, and the target element content was calculated.

[0173] 2.Co doping thickness The adhesive for sample preparation (PVDF was dispersed in N-methylpyrrolidone, the PVDF content is about 8%) and the sample powder were mixed uniformly (the powder weight is about 5 times that of the adhesive), then applied to copper foil and dried at 60℃ for 30min. The prepared sample was cut into 6mm*6mm size with scissors, fixed on the sample stage, and placed in an ion polisher (model number: IB-19500CP), and the sample edge was adjusted to the X-axis and Y-axis positions of 40-60μm parallel to the center line and cut. After cutting was completed, a combination of an X-Max type spectrometer (EDS) from Oxford Instruments Group in the UK and a Sigma-02-33 type scanning electron microscope (SEM) from ZEISS in Germany was used to select an appropriate particle cutting surface in the cut sample, linearly scan the Co element content along the particle diameter direction, and measure the distance from the particle center position to the part where the Co content begins to increase from the particle inner core and denote it as L1, and the Co doping thickness is (particle radius R-L1)μm.

[0174] 3. Amount of lithium impurities on the surface Acid-alkali titration method: 30g of sample was put into 100ml of pure water, stirred for 30min, and then allowed to stand for 5min. Then, it was extracted and filtered, and 10ml of the supernatant was taken. The lithium carbonate and lithium hydride dissolved in the positive electrode material were titrated with 0.05mol / L hydrochloric acid standard solution. A pH electrode was used as the indicator electrode, and the end point was determined by the potential change, and the amount of lithium impurities on the surface of the positive electrode material was calculated.

[0175] 4.Volume distribution particle size Test method for volume distribution particle size: Refer to GB / T 19077-2016 / ISO 13320:2009 Particle size distribution laser diffraction method, adopt the equipment Mastersizer 2000. Take a clean beaker, add the sample to be measured to the light shielding degree of 8%-12%, add 20ml of deionized water, and perform ultrasonic for 5min, then start the particle size tester to start the test.

[0176] Powder compaction density at 5.5 tonnes pressure The compaction density test method is to compact the sample with a pressure of 5 tons in a specific mold to obtain the thickness, and then measure ρ cThis involves calculating the packed density as follows: V = m / V = m / (S*H), where m is the material weight, S is the powder area and H is the powder height.

[0177] 6. Button battery manufacturing: The ternary positive electrode materials prepared in the above examples and comparative examples, PVDF, and conductive carbon are added to N-methylpyrrolidone in a weight ratio of 90:5:5, and stirred in a drying chamber to prepare a slurry. The slurry is applied to an aluminum foil, dried, and cold pressed to prepare a positive electrode plate. A lithium sheet is used as the negative electrode, and 1 mol / L LiPF is used as the electrolyte. 6 / (EC+DEC+DMC) (volume ratio: 1:1:1) and assembled into a button battery box.

[0178] Button battery initial gram capacity test method: Charge the battery at 2.8-4.3V at 0.1C up to 4.3V, then charge it at 4.3V with a constant voltage of ≦0.05mA, leave it for 2min, and measure the charge capacity as C 0 Then, discharge it at 0.1C to 2.8V. The discharge capacity at that time is the initial capacity, D 0 It was decided.

[0179] 7. Full battery manufacturing: The ternary positive electrode material manufactured in each of the above examples and comparative examples was used as the positive electrode active material, and the conductive agent acetylene black and the adhesive polyvinylidene fluoride (PVDF) were thoroughly mixed in an N-methylpyrrolidone solvent system in a weight ratio of 94:3:3, and then coated on an aluminum foil, dried, and cold pressed to obtain a positive electrode plate. The negative electrode active material artificial graphite, hard carbon, conductive agent acetylene black, adhesive styrene butadiene rubber (SBR), and thickener sodium carbon methyl cellulose (CMC) were thoroughly mixed in a deionized water solvent system in a weight ratio of 90:5:2:2:1, and then coated on a copper foil, dried, and cold pressed to obtain a negative electrode plate. A polyethylene porous polymer film was used as the separator. The positive electrode plate, separator, and negative electrode plate were stacked in order, and the separator was positioned in the center of the positive and negative electrodes to play the role of isolation, and then wound to obtain a bare cell. The bare cell is placed in the exterior case and the mixed base electrolyte, i.e. 1 mol / L LiPF 6 / (EC+EMC+DMC) (volume ratio: 1:1:1) was injected and packaged to obtain a whole battery.

[0180] Full battery initial gram capacity test method: In a constant temperature environment of 25℃, leave it for 5 minutes, discharge it at 1 / 3C to 2.8V, leave it for 5 minutes, charge it at 1 / 3C to 4.25V, and then charge it at a constant voltage of 4.25V until the current is ≦0.05mA, leave it for 5 minutes, and the charge capacity at that time is C 0 Then, discharge it at 1 / 3C to 2.8V. The discharge capacity at that time is the initial capacity, D 0 It was decided.

[0181] All batteries 25 / 45℃ cycle performance test: In a constant temperature environment of 25℃ or 45℃, charge at 2.8-4.25V at 1C to 4.25V, then charge at 4.25V with a constant voltage of ≦0.05mA, leave it for 5min, and discharge at 1C to 2.8V. The capacity is D 0 Then, repeat the previous process to obtain the capacity D n (n=0,1,2……) was recorded, and the capacity retention rate for 300 cycles: (D 300 -D 0 ) / D0 *100% calculated.

[0182] 8. Gas expansion test at 70℃ for all batteries: The cells were stored at 70℃ and 100% SOC (residual capacity). The OCV (open circuit voltage), IMP (impedance) and volume (drainage test) of the cells were measured before, during and after storage. After storage, the cells were tested for residual capacity and reversible capacity. The cells were taken out of the furnace every 48 hours and left to stand for 1 hour before testing the OCV and IMP. After cooling to room temperature, the cells were tested for volume using the drainage method. The test was completed after 30 days of storage, or when the volume expansion exceeded 50%, storage was stopped. The protection voltage range was 2.7-4.3V, and the nominal capacity was 2.25Ah.

[0183] The above examples and comparative examples were tested according to the above process, and the specific values ​​are shown in Tables 1 to 6.

[0184] [Table 1-1]

[0185] [Table 1-2]

[0186] [Table 2]

[0187] [Table 3]

[0188] [Table 4-1]

[0189] [Table 4-2]

[0190] [Table 5]

[0191] [Table 6]

[0192] As can be seen from Table 1, the 25°C and 45°C cycle capacity retention rates of all the full batteries corresponding to all the Examples were significantly higher than those of the Comparative Examples, and the gas expansion after storage at 70°C for 30 days was lower than that of all the Comparative Examples in all the Examples. In addition, in the case of the same ternary positive electrode material substrate, the 0.1C button battery capacity and 1 / 3C full battery capacity of the Examples were also significantly better than those of all the Comparative Examples.

[0193] Comparing Examples 1-1 to 1-3 comprehensively, when a high-nickel ternary positive electrode material substrate is doped with M1, M2 and W elements, and its surface layer is further doped with Co and further coated with an inner coating layer of a Co-containing compound and an outer coating layer of an Al-containing compound and a B-containing compound, the corresponding full-cell capacity retentions at 25°C cycle are all higher than 94.7%, and the capacity retentions at 45°C cycle are all higher than 91.5%, while the gas expansion after storage at 70°C for 30 days is all lower than 4.91 mL / Ah.

[0194] Comprehensively comparing Example 1-1 with Examples 2-1 to 2-3, when M1 is one of Mo, Zr, Ti, Sb, Nb, and Te, and M2 is one of Mg, Al, Ca, Zn, and Sr, the corresponding 0.1C button battery capacity, 1 / 3C total battery capacity, 25°C and 45°C cycle capacity retention, and gas expansion performance after storage at 70°C for 30 days were all good.

[0195] Comprehensively comparing Example 1-1 with Example 3-1 to Example 3-8, when the doping amount of W is 100-2000 ppm, the doping amount of M1 is 2000-4000 ppm, the doping amount of M2 is 500-2000 ppm, and the ratio of the doping amount of M1 to the sum of the doping amounts of M2 and W is 1:(0.1-2), the corresponding 0.1C button battery capacities are all higher than 222.4mAh / g, the 1 / 3C total battery capacities are all higher than 211.2mAh / g, the 25°C cycle capacity retentions are all higher than 94.5%, and the 45°C cycle capacity retentions are all higher than 91.2%, while the gas expansion after storage at 70°C for 30 days is all lower than 5.01mL / Ah. Furthermore, when the ratio of the doping amount of M1 to the sum of the doping amounts of M2 and W is 1:(0.5-1.5), the corresponding 0.1C button battery capacity, 1 / 3C full battery capacity, 25℃ and 45℃ cycle capacity retention and gas expansion performance after storage at 70℃ for 30 days are further improved.

[0196] Comprehensively comparing Example 1-1 with Example 4-1 to Example 4-12, when the sum of the surface doping amount of Co and the coating amount of the Co-containing compound is 100-20000ppm, the coating amount of the Al-containing compound is 100-3000ppm, and the coating amount of the B-containing compound is 100-2000ppm, the coating amount of the Al-containing compound and the coating amount of the B-containing compound satisfy the weight ratio of Al to B being (0.5-2):1, and when the sum of the surface doping amount of Co and the coating amount of the Co-containing compound, the Al-containing compound and the B-containing compound is 1000-22000ppm, the corresponding 0.1C button battery capacity, 1 / 3C total battery capacity, 25℃ and 45℃ cycle capacity retention rate and gas expansion performance after storage at 70℃ for 30 days are all good. Furthermore, when the sum of the surface doping amount of Co and the coating amount of the Co-containing compound, the Al-containing compound and the B-containing compound is 1000-15000 ppm, the corresponding 0.1C button battery capacity, 1 / 3C total battery capacity, and 25°C and 45°C cycle capacity retention are further improved.

[0197] As can be seen from Table 5, when the sintering temperature in step S1 is 700-950°C, the 0.1C button battery capacity, 1 / 3C full battery capacity, 25°C and 45°C cycle capacity retention, and gas expansion performance after storage at 70°C for 30 days corresponding to the prepared ternary positive electrode material are good, and if the initial sintering temperature is too high or too low, it will obviously affect the capacity, cycle and storage gas expansion performance of the prepared ternary positive electrode material.

[0198] As can be seen from Table 6, when the sintering temperature in step S2 is 500-800°C, the 0.1C button battery capacity, 1 / 3C full battery capacity, 25°C and 45°C cycle capacity retention rate and gas expansion performance after storage at 70°C for 30 days corresponding to the prepared ternary positive electrode material are good. When the temperature in step S2 is too high, Co is basically all doped into the particles, which greatly changes the composition of the whole particle and reduces the nickel content in the whole material particles, thereby obviously reducing the capacity of the material and the amount of Co-containing compound coated on the surface is small, which affects the cycle and storage performance of the battery. When the temperature in step S2 is too low, Co-containing compound is basically all coated on the surface of the particles and does not react well with the lithium impurities on the particle surface, so the lithium impurities are relatively high and the Co-containing compound does not react with the lithium impurities, which makes the Co-containing compound inactive, resulting in a low capacity of the whole material and affecting the cycle and storage performance of the battery.

[0199] It should be noted that the present application is not limited to the above-mentioned embodiment. The above-mentioned embodiment is merely an example, and any embodiment having substantially the same configuration as the technical idea and achieving the same effect within the scope of the technical solution of the present application is included in the technical scope of the present application. In addition, various modifications that a person skilled in the art can make to the embodiment and other methods constructed by combining some of the components in the embodiment are also included in the scope of the present application, within the scope of the purpose of the present application. [Explanation of symbols]

[0200] 1 battery pack, 2 upper housing, 3 lower housing, 4 battery module, 5 secondary battery, 51 case, 52 electrode assembly, 53 cover plate.

Claims

1. A modified high nickel ternary positive electrode material, comprising an inner core and two coating layers, The inner core comprises a high nickel ternary cathode material substrate, the substrate being doped with M1, M2 and W, where M1 is one of Mo, Zr, Ti, Sb, Nb and Te, and M2 is one of Mg, Al, Ca, Zn and Sr, and the chemical formula of the high nickel ternary cathode material substrate doped with M1, M2 and W is Li 1+a [Ni x Co y Mn z M1 b M2 c W d ]O 2 where 0.65≦x<1, 0≦y<0.3, 0≦z<0.3, 0<a<0.2, 0<b<0.1, 0<c<0.1, 0<d<0.1, and x+y+z+b+c+d=1; The surface layer of the inner core is also doped with Co, A modified high nickel ternary positive electrode material, wherein the inner coating layer is a Co-containing compound, and the outer coating layer is an Al-containing compound and a B-containing compound.

2. 2. The modified high nickel ternary cathode material of claim 1, wherein the doping amount of M1 is greater than or equal to the doping amount of M2 or W.

3. 2. The modified high nickel ternary cathode material as claimed in claim 1, wherein the ratio of the doping amount of M1 to the sum of the doping amounts of M2 and W is 1:(0.1-2).

4. 2. The modified high-nickel ternary cathode material of claim 1, wherein the thickness d of the surface layer is 0<d<3 μm.

5. The modified high nickel ternary cathode material according to claim 1, characterized in that the sum of the surface doping amount of Co and the coating amount of the Co-containing compound is 100-20000 ppm, the coating amount of the Al-containing compound is 100-3000 ppm, and the coating amount of the B-containing compound is 100-2000 ppm, wherein the surface doping amount and the coating amount are all calculated in terms of the corresponding element in the compound for the modified high nickel ternary cathode material.

6. The modified high nickel ternary positive electrode material according to claim 1, characterized in that the total thickness of said inner and outer coating layers is 0.001-1 μm.

7. The modified high nickel ternary cathode material according to claim 1, characterized in that the coating amount of the Al-containing compound and the coating amount of the B-containing compound satisfy a weight ratio of Al to B of (0.5-2):1, wherein each of the coating amounts is calculated as a corresponding element in the compound for the modified high nickel ternary cathode material.

8. 2. The modified high nickel ternary cathode material of claim 1, wherein the doping amount of W is 100-2000 ppm, the doping amount of M1 is 2000-4000 ppm, and the doping amount of M2 is 500-2000 ppm, wherein the doping amounts are all calculated as corresponding elements for the modified high nickel ternary cathode material.

9. The modified high nickel ternary cathode material according to claim 1, characterized in that the sum of the surface doping amount of Co and the coating amount of the Co-containing compound, the Al-containing compound and the B-containing compound is 1000-22000 ppm, wherein the surface doping amount and the coating amount are all calculated in terms of the corresponding element in the compound for the modified high nickel ternary cathode material.

10. The volume particle size distribution diameter distance is (Dv 90 -Dv 10 ) / Dv 50 2. The modified high nickel ternary cathode material of claim 1, wherein the ternary cathode material satisfies the following:

11. 2. The modified high nickel ternary cathode material of claim 1, characterized in that its powder compaction density at 5 tons pressure is > 3.4 g / cc.

12. 1. A method for producing a modified high nickel ternary cathode material, comprising: Mixing lithium salt, W-doped high nickel ternary precursor, M1-containing compound and M2-containing compound, and sintering at a sintering temperature of 700-950°C to obtain M1, M2 and W-doped high nickel ternary positive electrode material substrate, wherein the W-doped high nickel ternary precursor has a chemical formula of (Ni X Co Y Mn Z W D ) (OH) 2 wherein 0.65≦X<1, 0≦Y<0.3, 0≦Z<0.3, 0<D<0.1, M1 is one of Mo, Zr, Ti, Sb, Nb, and Te, M2 is one of Mg, Al, Ca, Zn, and Sr, and the chemical formula of the high nickel ternary positive electrode material substrate doped with M1, M2, and W is Li 1+a [Ni x Co y Mn z M1 b M2 c W d ]O 2 Step S1, where 0.65≦x<1, 0≦y<0.3, 0≦z<0.3, 0<a<0.2, 0<b<0.1, 0<c<0.1, 0<d<0.1, and x+y+z+b+c+d=1; Step S2: mixing the high-nickel ternary positive electrode material substrate doped with M1, M2 and W with a Co-containing compound, and sintering the mixture at a sintering temperature of 500-800° C. to obtain a high-nickel ternary positive electrode material whose surface is doped with Co and whose surface is covered with a Co-containing compound; and step S3 of mixing the high-nickel ternary positive electrode material, the surface of which is doped with Co and coated with a Co-containing compound, with an Al-containing compound and a B-containing compound, and sintering the mixture to obtain a modified high-nickel ternary positive electrode material.

13. In step S1, the sintering time is 10-20 h, and the sintering atmosphere is air or O 2 13. The method of claim 12, wherein:

14. 13. The method of claim 12, wherein the particle size of the Co-containing compound is 0.001-10 μm.

15. In step S2, the sintering time is 5-15 h, and the sintering atmosphere is air or O 2 13. The method of claim 12, wherein:

16. In step S3, the sintering temperature is 200-500° C., the sintering time is 5-15 h, and the sintering atmosphere is air or O 2 13. The method of claim 12, wherein:

17. 12. A secondary battery comprising the modified high nickel ternary cathode material of any one of claims 1 to 11.

18. A battery module comprising the secondary battery according to claim 17.

19. A battery pack comprising the battery module according to claim 18.

20. A power consuming device comprising the secondary battery of claim 17.

Citation Information

Patent Citations

  • Anode material for nickel-base lithium ion battery and preparation method of anode material

    CN104409700A

  • High-nickel ternary material with cobalt-rich surface layer and preparation method and application thereof

    CN106898751A

  • Method for coating high-nickel ternary material with aluminum oxide and boron oxide

    CN108091830A

  • Lithium ion battery cathode material and preparation method thereof, cathode and lithium ion battery

    CN109461926A

  • Positive electrode active material and preparation method thereof, positive electrode plate and lithium ion secondary battery

    CN112447950A